Surveilling the Revolutionaries: Armenian Revolutionaries, Spatial Politics, and Intelligence Activities in the Late Nineteenth-Century Ottoman Empire - Arda Akıncı (Mashriq & Mahjar, 2022)
This paper, by focusing on a secret report delivered by the Ottoman High Commissioner in Egypt—Gazi Ahmed Muhtar Pasha—to the imperial center regarding the Armenian revolutionaries’ movements, aims to examine three important phenomena of the late Ottoman history. The first goal is to reveal the revolutionary mobilities in the late Ottoman Empire by tracking how said revolutionaries took advantage of the borderlands to mobilize themselves. Second, this particular research serves as an indicator of the spatial politics in the late nineteenth-century Ottoman Empire by exposing how the imperial center governed a multi-layered administrative borderland region of Egypt—a semi-autonomous Khedivate. Finally, this paper seeks to confront traditional historiography on the intelligence activities during the reign of Abdülhamid II (r. 1876–1909). By doing so, this paper demonstrates how the intelligence organization stretched from the administrative center to the frontiers and borderlands of the Ottoman Empire, contrary to the common assumptions in the existing literature.